O Canal Rural no espaço agrícola de Cruz Alta - Culau, Denise de Castro (2006)
In the beggining, the Rural Channel, transmitted to be received through parabolic antenna, stayed the public close to with possibilities of specific reception for the farming way and accomplishing, like this, a certain extensive character. The significant changes in the way of transmission of the analogical sign (received by any parabolic antenna) to digital, doing with that only who roots television subscriber to cable, or subscriber of the system Net/Sky, could receive the sign of the broadcasting station, carted a re-evaluation of the programming content, with the purpose of adapting the performance to the new public's interest (predominantly urban), and restricting the inclusion area. With the exit of Rural Channel of the “C” band transmission, was smuggled of the programming with outstanding his extensive character, the small and medium rural producer, carting lack of information in his activity context; stopping accomplishing, like this, with his role of extension vehicle, not could be supplied, short term, for other communication means.